Functional VEGFA knockdown with artificial 3′-tailed mirtrons defined by 5′ splice site and branch point - Kock, Kian Hong (2015)
Mirtrons are introns that form pre-miRNA hairpins after splicing to produce RNA interference (RNAi) effectors distinct from Drosha-dependent intronic miRNAs, and will be especially useful for co-delivery of coding genes and RNAi. A specific family of mirtrons – 3′-tailed mirtrons – has hairpins precisely defined on the 5′ end by the 5′ splice site and 3′ end by the branch point. Here, we present design principles for artificial 3′-tailed mirtrons and demonstrate, for the first time, efficient gene knockdown with tailed mirtrons within eGFP coding region. These artificial tailed mirtrons, unlike canonical mirtrons, have very few sequence design restrictions. Tailed mirtrons targeted against VEGFA mRNA, the misregulation of which is causative of several disorders including cancer, achieved significant levels of gene knockdown. Tailed mirtron-mediated knockdown was further shown to be splicing-dependent, and at least as effective as equivalent artificial intronic miRNAs, with the added advantage of very defined cleavage sites for generation of mature miRNA guide strands. Further development and exploitation of this unique mirtron biogenesis pathway for therapeutic RNAi coupled into protein-expressing genes can potentially enable the development of precisely controlled combinatorial gene therapy.